Conventional Chemotherapy and Inflammation: What Is the Role of the Inflammasome in the Tumor Microenvironment? - Chiara Colarusso; Michela Terlizzi; Simone Di Caprio; Anna Falanga; Emmanuel D’Andria; Roberta d’Emmanuele di Villa Bianca; Rosalinda Sorrentino (Biomedicines)
The link between inflammation and cancer has been extensively studied over the years. While the inflammatory process can facilitate tumor establishment and progression, on the other hand, current clinical approaches aim to boost the immune system against the tumor mass. In this scenario, the conventional chemotherapy has proven to induce immunogenic cell death in that the release of danger-associated alarmins can foster the cytotoxic immunity following the blockade of immune checkpoints. The release of alarmins can activate the inflammasome pathway. Thus, one of the questions is as follows: can conventional anti-tumor drugs lead to inflammasome activation? And if so, is the resulting effect anti- or pro-tumor? In this review, we provide an overview on the role of the inflammasome in cancer.